HLA-DRB115: 02 Is Associated With Iodinated Contrast Media-Related Anaphylaxis - Chung, Soo Jie; Kang, Dong Yoon; Lee, Whal; Lee, Seung Bok; Kim, Sujeong; Lee, Seung-Eun; Sim, Da Woon; Kang, Min-Gyu; Park, Kyung Hee; Jung, Jae-Woo; Yun, James; Kang, Hye-Ryun (Investigative radiology, 2020)
The incidence of severe reaction induced by iodinated contrast media (ICM) has increased over the years with an increasing use of imaging modalities. Although ICM anaphylaxis is rare, it can be life-threatening, but currently, there is no biomarker that can identify individuals at risk of ICM anaphylaxis. The aim of this study is to investigate the genetic susceptibility of ICM anaphylaxis. Patients who had ICM anaphylaxis were enrolled in the study, and their blood samples were collected for genotyping of human leukocyte antigen (HLA)-A, -B, -C, and -DR. The results were compared with those of healthy Korean general population. MRGPRX2 gene in ICM anaphylaxis group was also sequenced and compared with the Korean standard database of genetic polymorphism. The frequencies of 3 HLA alleles (B*52:01, C*12:02, and DRB1*15:02) were significantly higher in 47 patients with ICM anaphylaxis. In particular, HLA-DRB1*15:02 was 5 times more frequent in the ICM anaphylaxis group than the Korean general population (34.0% vs 6.6%; odds ratio, 7.306; 95% confidence interval, 3.622-14.740), and this difference was most pronounced in subjects with iohexol-induced anaphylaxis (odds ratio, 16.516; 95% CI, 5.241-52.047; P < 0.0001). Eight single nucleotide polymorphisms were identified in MRGPRX2 gene, but their frequencies were not different in those with ICM anaphylaxis compared with the general Korean population. HLA-DRB1*15:02 is associated with ICM anaphylaxis in the Korean population.